Kedudukan Ahli Waris Pengganti dalam Perspektif Hukum Islam dan Hukum Perdata di Indonesia - Rahman, Babur; Quthny, Abu Yazid Adnan; Firdausiyah, Vita (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abstract: This study discusses the position of substitute heirs from the perspective of Islamic law and civil law in Indonesia. In inheritance practices, situations often occur where direct heirs have died before the testator, so that problems arise regarding who inherits the inheritance. Islamic law recognizes the concept of hijab and the division of inheritance strictly based on lineage, but does not explicitly regulate substitute heirs. On the contrary, the Civil Code (KUHPerdata) and the Compilation of Islamic Law (KHI) provide space for grandchildren as substitute heirs, especially if their parents who should be heirs have died first. Through a normative-comparative approach, this study reveals that there are differences in principle between classical Islamic law and positive law in Indonesia regarding the existence of substitute heirs. KHI as a codification of Islamic law in Indonesia tries to accommodate the principle of social justice by adopting the concept of substitute heirs, although it is not entirely in accordance with classical fiqh. This study recommends the need for harmonization between Islamic legal norms and the provisions of national laws and regulations in order to ensure legal certainty and justice in the distribution of inheritance.Keywords: Substitute heir, Islamic law, civil law, KHI, inheritanceAbstrak: Penelitian ini membahas kedudukan ahli waris pengganti dalam perspektif hukum Islam dan hukum perdata di Indonesia. Dalam praktik pewarisan, sering kali terjadi situasi di mana ahli waris langsung telah meninggal dunia terlebih dahulu dari pewaris, sehingga muncul permasalahan mengenai siapa yang mewarisi harta peninggalan. Hukum Islam mengenal konsep hijab dan pembagian warisan secara tegas berdasarkan garis nasab, namun tidak secara eksplisit mengatur ahli waris penggantinya. Sebaliknya, Kitab Undang-Undang Hukum Perdata (KUHPerdata) dan Kompilasi Hukum Islam (KHI) memberikan ruang bagi cucu sebagai ahli waris pengganti, terutama jika orang tua mereka yang seharusnya menjadi ahli waris telah meninggal dunia lebih dahulu. Melalui pendekatan normatif-komparatif, penelitian ini mengungkap bahwa terdapat perbedaan prinsip antara hukum Islam klasik dengan hukum positif di Indonesia terkait keberadaan ahli waris pengganti. KHI sebagai kodifikasi hukum Islam di Indonesia mencoba mengakomodasi prinsip keadilan sosial dengan mengadopsi konsep ahli waris pengganti, meskipun tidak sepenuhnya sesuai dengan fiqh klasik. Kajian ini merekomendasikan perlunya harmonisasi antara norma-norma hukum Islam dan ketentuan peraturan perundang-undangan nasional guna menjamin kepastian hukum dan keadilan dalam pembagian warisan.Kata kunci: Ahli waris pengganti, hukum Islam, hukum perdata, KHI, pewarisan